The performance of mutual funds in Ghana: a case study of Anidaso mutual fund 2006-2008 - Obeng, Obed Joy (2014)
A thesis submitted to Business School, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration,